2022
DOI: 10.1038/s41598-022-07246-9
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study on the impact of working environment on the well-being of teachers in China’s private colleges

Abstract: Teacher well-being is a prominent issue in policy and public debates. Those teachers working in private schools deserve concern given concerns about their working environment. Focus of this study: to learn about the level and main characteristics of teacher well-being in private schools and to explore the impact of working environment on their well-being. Methodology: The data were collected via an online questionnaire among 1161 language teachers at 58 China’s private colleges in 22 provinces, and were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Leadership is a key aspect to influence, push and motivate others by enhancing their abilities and capabilities in performing and completing a task in lined with previous studies [11]- [13]. A strong and supportive leadership team, as well as strong financial and technical support from stakeholders, may assist to boost the influence not just on academics and outcomes, but also on individual well-being [31].…”
Section: Discussionsupporting
confidence: 65%
“…Leadership is a key aspect to influence, push and motivate others by enhancing their abilities and capabilities in performing and completing a task in lined with previous studies [11]- [13]. A strong and supportive leadership team, as well as strong financial and technical support from stakeholders, may assist to boost the influence not just on academics and outcomes, but also on individual well-being [31].…”
Section: Discussionsupporting
confidence: 65%
“…For example, Vithanage and Arachchige found that female teachers scored slightly higher on WLB than male teachers [ 41 ], while other studies showed that male teachers had better WLB than female teachers [ 40 ]. Some studies found that female college teachers had higher WB scores than male teachers [ 44 , 45 ], while other studies found that college teachers’ perceptions of WB showed no significant gender difference [ 46 ]. In addition, some studies have found no gender difference in the EE scores of college teachers [ 48 ], while another study found that male teachers in local universities had stronger perceptions of EE than female teachers [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that male teachers had stronger perceptions of WLB than female teachers [ 38 , 39 , 40 ], while other studies found that male teachers’ perceptions of WLB were weaker than those of female teachers [ 41 ], and yet others found no gender difference [ 42 , 43 ]. Similarly, some studies have shown that women have stronger perceptions of WB than men [ 44 , 45 ], but another study found no gender difference [ 46 ]. As for the perception of EE, studies have found no gender difference among college teachers [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found that poor well-being leads to stress [22][23][24]. Meanwhile, high stress and low well-being usually cause poor performance and excessive fatigue [25][26][27]. It was observed in Malaysia that 90% of teachers consider resignation due to high-stress levels [28].…”
Section: Introductionmentioning
confidence: 99%